An international survey on the role of the hospital transfusion committee. Issue 5 (24th February 2017) - Yazer, Mark H.; Lozano, Miguel; Fung, Mark; Kutner, Jose; Murphy, Michael F.; Oveland Apelseth, Torunn; Pogłód, Ryszard; Selleng, Kathleen; Tinmouth, Alan; Wendel, Silvano; Yahalom, Vered; ,
Abstract : BACKGROUND: Hospital transfusion committees (HTCs) can oversee all aspects of transfusion practice at a hospital. This survey sought to identify which quality variables were being reported at HTCs around the world. STUDY DESIGN AND METHODS: A working party composed of members of the Biomedical Excellence for Safer Transfusion (BEST) collaborative developed a survey of quality variables that could be potentially presented at HTC meetings. The survey was electronically sent to all BEST members who were encouraged to complete it if they were active on an HTC and to send it to other colleagues with similar experience. An expert panel was convened to determine which quality variables are the most important for review at HTC meetings. RESULTS: There were 121 respondents; the majority were from Europe (52%), Asia (19%), or North America (19%). Most respondents (68%) were at university hospitals. Of the 117 (97%) respondents with an HTC, the committee most often met quarterly (42%) and reviewed transfusion reactions (79%) and risk management–reported events (52%). The HTCs most commonly included transfusion medicine physicians, anesthesiologists, and other physicians who regularly transfuse blood products. Some of the most commonly reported quality variables included number of blood products transfused, wasted, and expired and the number of improperly labeled specimens. The expert panel analysis revealed that some variables that were deemed important were not being frequently reported at HTCs. CONCLUSION: There is variability in the variables being reported at HTCs around the world with some important variables not frequently reported.